Van der Valk. Season 2 [videorecording (DVD)] - Murray, Chris (Screenwriter) (PBS Distribution, 2022)
Van der Valk and the team return for a second compelling season of murder investigations set against the stunning backdrop of Amsterdam and its contrasting worlds.